2019
DOI: 10.1016/j.cub.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Emergence of Hippocampal Replay and Theta Sequences during Post-natal Development

Abstract: Summary Hippocampal place cells encode an animal’s current position in space during exploration [ 1 ]. During sleep, hippocampal network activity recapitulates patterns observed during recent experience: place cells with overlapping spatial fields show a greater tendency to co-fire (“reactivation”) [ 2 ], and temporally ordered and compressed sequences of place cell firing observed during wakefulness are reinstated (“replay”) [ 3 ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 45 publications
5
52
0
Order By: Relevance
“…While stable place cells are present as early as postnatal day (P) 16 in rats (Langston et al, ; Wills, Cacucci, Burgess, & O'Keefe, ), they appear insufficient to support navigation according to spatial context. Supporting this notion, sequential firing of place cells along trajectories associated with online navigation, and their temporally compressed replay during immobility and sleep, does not emerge until after the third postnatal week (Farooq & Dragoi, ; Muessig, Lasek, Varsavsky, Cacucci, & Wills, ). Given the role of gamma oscillations in coordinating place cell ensemble activity in adults, in addition to other aspects of spatial information processing, it is possible that changes in gamma oscillations during the third postnatal week are necessary to enable spatial navigation ability.…”
Section: Introductionmentioning
confidence: 99%
“…While stable place cells are present as early as postnatal day (P) 16 in rats (Langston et al, ; Wills, Cacucci, Burgess, & O'Keefe, ), they appear insufficient to support navigation according to spatial context. Supporting this notion, sequential firing of place cells along trajectories associated with online navigation, and their temporally compressed replay during immobility and sleep, does not emerge until after the third postnatal week (Farooq & Dragoi, ; Muessig, Lasek, Varsavsky, Cacucci, & Wills, ). Given the role of gamma oscillations in coordinating place cell ensemble activity in adults, in addition to other aspects of spatial information processing, it is possible that changes in gamma oscillations during the third postnatal week are necessary to enable spatial navigation ability.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, spatial activity in the rodent hippocampus is strongly modulated by continuous theta oscillations (5-12 Hz) during locomotion (Vanderwolf, 1969;Buzsáki, 2005). The resulting 'phase precession,' a monotonic advance in timing from late to early within each theta cycle, may enhance the precision and temporal organization of spatial codes (O'Keefe and Recce, 1993;Jensen and Lisman, 2000;Foster and Wilson, 2007;Drieu et al, 2018) in ways that support decisionmaking and/or deliberative planning during subsequent sleep or quiescent states (Buzsáki, 1989;Johnson and Redish, 2007;Buzsáki and Moser, 2013;Wikenheiser and Redish, 2015;Papale et al, 2016;Muessig et al, 2019). Recently, in contrast to phase precession, we discovered a novel class of spatial phase-coding neurons in open field environments termed 'phaser cells' that were located predominantly in the rat lateral septum and characterized by a strong coupling of theta-phase timing to firing rates (Monaco et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…But the question of why we struggle to remember even the most salient events from our early lives remains poorly understood. A new study by Muessig et al [2], reported in this issue of Current Biology, delivers fresh insight into how the hippocampal processes thought to underlie memory evolve during development, providing an answer to this long-standing question.…”
mentioning
confidence: 99%
“…In the new study, Muessig et al [2] set out to explain the temporal discrepancy that exists between the place coding present even in the very young mammalian hippocampus and the delayed emergence of hippocampal-dependent memory. They took a systematic approach, detailing the key processes involved -place coding, theta sequences and replayand characterizing their progression through early development to their final, stable endpoint in young adulthood.…”
mentioning
confidence: 99%
See 1 more Smart Citation